Matematyka 2 gimnazjum :))
1)Wykonaj redukcję wyrazów podobnych:
a-2a²+5-3a+4a²-3
3y²-3y+3y-y²+6
⅔x²- ⅔x+ ⅓x²- ⅓x
0,3c³ - 0,2c²- 0,6c³+ c²
5d²-1,5d³- ½d²-0,8+d³- 2,2
3ab- 5a²b²- 6ab²+2ab+ab²+7a²b²

2)Wykonaj odejmowanie:
(-12abc- 4a²bc) - (abc+a²bc) + 12
(1⅗x³+ ⅔y² -⅚) -(2,4x³+ y²- ¹/₆)
(0,4ab - 0,5bc+ 0,1cd) - (-0,3ab+ 2,5bc - cd)

3)Wykonaj dodawanie
(y²+ 5y- 6)+ (2y²-y+8)
(5x²-ax+a²)+ (3x²+2ax-3a²)



2

Odpowiedzi

  • Tess
  • Początkujący
2009-11-23T20:42:00+01:00
1)
a-2a²+5-3a+4a²-3=-2a-2a²+2
3y²-3y+3y-y²+6=2y²=6
⅔x²- ⅔x+ ⅓x²- ⅓x=1x²+⅓x
0,3c³ - 0,2c²- 0,6c³+ c²=-0,3³-0,2c²
5d²-1,5d³- ½d²-0,8+d³- 2,2=4,5d²-0,5d³-0,8
3ab- 5a²b²- 6ab²+2ab+ab²+7a²b²=5ab+2a²b²-5ab²
2)

(-12abc- 4a²bc) - (abc+a²bc) + 12=-12abc-4a²bc-abc-a²bc=-13abc-5a²-abc
(1⅗x³+ ⅔y² -⅚) -(2,4x³+ y²- ¹/₆)=1⅗x³+ ⅔y² -⅚ +2,4x³- y²+ ¹/₆=(hmm.. nie wiem co dalej ;/)
(0,4ab - 0,5bc+ 0,1cd) - (-0,3ab+ 2,5bc - cd)=0,4ab - 0,5bc+ 0,1cd+0,3ab - 2,5bc + cd=1,1cd+ 0,3ab- 2,5bc

3)

(y²+ 5y- 6)+ (2y²-y+8)=3y²+4y+2
(5x²-ax+a²)+ (3x²+2ax-3a²)=8x²+ax-2a²
1 1 1
2009-11-23T20:46:34+01:00
A-2a²+5-3a+4a²-3 = -2a+2a²+2
3y²-3y+3y-y²+6 = 2y²+6
⅔x²- ⅔x+ ⅓x²- ⅓x= x² -x
0,3c³ - 0,2c²- 0,6c³+ c² = -0,3c³ + 0,2²
5d²-1,5d³- ½d²-0,8+d³- 2,2 = 4,5d²-0,5d³ - 2,2
3ab- 5a²b²- 6ab²+2ab+ab²+7a²b² = 5ab +2a²b²-5ab²

2)Wykonaj odejmowanie:
(-12abc- 4a²bc) - (abc+a²bc) + 12 = -12abc-4a²bc-abc-a²bc+12=-13abc-5a²bc+12
(1⅗x³+ ⅔y² -⅚) -(2,4x³+ y²- ¹/₆)= 15x³+2/3y²-5-2,4x³-y²+1/6 = 12,6x²-5/3y² +1/6
(0,4ab - 0,5bc+ 0,1cd) - (-0,3ab+ 2,5bc - cd) = 0,4ab-0,5bc+0,1cd+0,3ab-2,5bc+cd=0,7ab-2bc+1,1cd

3)Wykonaj dodawanie
(y²+ 5y- 6)+ (2y²-y+8) = 3y²+4y+2
(5x²-ax+a²)+ (3x²+2ax-3a²)= 8x²+ax-2a²